Problems of holistic nature education in sustainable development concepts - Sandner, Jan (Studia Ecologiae et Bioethicae, 2007)
In the article, the author is trying to find quintessential causes for the said errors, the article touches on the difficult problematic issues from the borderline of various areas of study relating to learning about the environment, the primary concept of the author is the attempt to undertake a holistic approach to the problem of natural science education. M s approach is to guarantee a better understanding of the environment. It is also to impact the launch of a new quality of its management and solve the growing number of critical situations in the environment and by the same, the proper shaping and implementation of the sustainable environment concept. In his presentation, the author backs his arguments with well known views of the following philosophers: Forbes, Smuts, Tansley, Haeckel, Birge as well as with theories from the borderline of ecology and philosophy such as: the development theory, integration levels and synergism.